Synthesis, structural characterization, in vitro comparative DNA/RNA binding, and computational studies of half-sandwich Ru (II)(ƞ6-p-cymene) aminoquinoline complex. (1st February 2022) - Akhter, Suffora; Usman, Mohammad; Arjmand, Farukh; Tabassum, Sartaj
Graphical abstract: Synthesis and characterisation of half-sandwich Ru(II)( ƞ 6 - p - cymene) complex 1 containing aminoquinoline ligand. Comparative ct-DNA/tRNA binding studies of the complex 1 were performed by employing UV–vis, fluorescence, circular dichroism, and cyclic voltametric techniques which indicated stronger binding affinity of the complex 1 towards ct-DNA. Cytotoxic activity against three human cancer cell lines was also carried out. DFT calculations were performed to generate the UV and IR spectra of the complex which further supported the experimental data. Molecular modeling approach was also applied to probe the binding-conformation of the complex with ct-DNA/tRNA. Abstract: We describe herein, synthesis of a half-sandwich Ru (II)( ƞ 6 - p - cymene) complex 1 containing aminoquinoline ligand. Complex 1 was characterized by various spectroscopic and single-crystal X-ray crystallographic techniques. The "piano-stool" complex crystallizes in a triclinic P 1 ¯ space group with ruthenium (Ⅱ)( p - cymene) fragment tethered to a primary amine nitrogen atom of aminoquinoline. DFT calculations were performed to generate UV and IR spectra of complex 1 which further supported the experimental data. Comparative DNA/RNA binding studies of the complex were carried out by employing UV–vis, fluorescence, circular dichroism, and cyclic voltammetric techniques. The intrinsic binding constants of the complex 1 with ct-DNA and tRNA were calculated to be 3.9 × 10 5 (±0.09) M −1 and 2.45 × 10 4 (±0.10) M −1 which indicated a stronger binding affinity of the complex 1 towards ct-DNA. The pBR322 plasmid scissoring efficiency of the complex was explored by performing gel electrophoresis. The results suggested that the complex induced double-stranded DNA cleavage at 35 μM concentration which is mediated via an oxidative pathway. RNA gel fragmentation assay was also performed in both concentration and time-dependent manner and an appreciable reduction in the intensity of the bands was observed after 24 hr incubation which demonstrated complete cleavage of the tRNA. BSA and lysozyme binding studies of the complex were also carried out and the results revealed that complex 1 quenched the fluorescence intensity of the proteins. Cytotoxicity studies revealed low cytotoxicity against three human cancer cell lines. Furthermore, molecular modeling approach was applied to probe the binding-conformation of the complex with ct-DNA/tRNA and the results showed that complex 1 exhibited preferential binding propensity towards ct-DNA.